ANALYSIS OF FACTORS AFFECTING COMPANY PERFORMANCE WITH PROFIT MANAGEMENT AS INTERVENING VARIABLES IN MANUFACTURING INDUSTRIES OF CONSUMPTION GOODS LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2013-2016 - Vany, Nurul Haj (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of firm size, leverage, firm growth, institutional ownership, managerial ownership on firm performance with earnings management as intervening variable on manufacturing companies in the consumer goods sector in companies listed in the Indonesia Stock Exchange in the period of 2013-2016. The samples were 23 companies, taken by using purposive sampling technique for the population of 37 companies. Secondary data were gathered like annual financial statement publicized in website www.idx.co.id.The gathered data were analyzed by using by using multiple linier regression analysis and path anlysis. The result of the research showed thatfirm size, leverage, firm growth, institutional ownership, managerial ownership simultaneously had significant influence on the firm performance on manufacturing companies in the consumer goods sector listed in the Indonesian Stock Exchange. Partially, firm size had positive and significant on firm performance, and manajerial ownership had negative and significant on firm performance, while leverage, firm growth, institutional ownership did not have any significant influance in firm performance. Earnings managamant had positive and significant on firm performance. Based on the result of Baron and Kenny test on the variable firm size, leverage, firm growth, it was found that earnings management did not act as intervening variable, while the result of Baron and Kenny test on the variable of institutional ownership and managerial ownership showed that earnings management acted as intervening variable.